ANALISIS KESALAHAN KEBAHASAAN DALAM TEKS PROSEDUR TABLOID NOVA - Anggraini, Nabila Syifa; Inderasari, Elen (Hasta Wiyata, 2024)
The phenomenon of language errors is still found in several tabloids, one of which is the Nova tabloid. There are still many grammatical errors found in the procedural text presented in the Nova tabloid, especially in the “Sedap Sedap” section. This study aims to explain the form of language errors in the procedural text of the Nova tabloid "Snack Sedap" rubric, May 26-June 22, 2022 edition. This study used a qualitative descriptive method with a type of literature study. The results of research and data analysis in this study found 226 language errors. The mistakes are the use of imperative sentences, the use of temporal conjunctions, the use of final conjunctions, material verbs and errors in the use of diction.